1977
DOI: 10.1084/jem.145.2.460
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol myristate acetate: a mitogen selective for a T-lymphocyte subpopulation.

Abstract: Phorbol myristate acetate (pma) is a potent mitogen for human peripheral blood lymphocytes (PBL) comparable to phytohemagglutinin (PHA) in potency. Inactivation of PHA-responsive lymphocytes by 5'-bromodeoxyuridine and light treatment left the PMA response intact and nice versa. Experiments separating lymphocytes by rosetting with sheep erythrocytes (SRBC) demonstrated that the PMA-responsive lymphocytes segregate with those that have a high affinity for SRBC to a greater than PHA- or concanavalin A (Con A)-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
1

Year Published

1978
1978
1987
1987

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(48 citation statements)
references
References 14 publications
5
42
1
Order By: Relevance
“…Protein kinase C is thought to account for all or most of the biological events that occur after treatment of cells with PMA (45). In previous studies that used primary cultures of unfractionated PBL, PMA was reported to be a T-cell mitogen with a potency approximately one-third that of the lectin PHA (58). After treatment of purified CD28+ cells with PMA only, thymidine incorporation was only slightly above the baseline ( Table 1), indicating that PMA is a comitogen for T cells, and that "accessory" cells (monocytes) are required for PMA to cause T-cell proliferation (10).…”
Section: Resultsmentioning
confidence: 99%
“…Protein kinase C is thought to account for all or most of the biological events that occur after treatment of cells with PMA (45). In previous studies that used primary cultures of unfractionated PBL, PMA was reported to be a T-cell mitogen with a potency approximately one-third that of the lectin PHA (58). After treatment of purified CD28+ cells with PMA only, thymidine incorporation was only slightly above the baseline ( Table 1), indicating that PMA is a comitogen for T cells, and that "accessory" cells (monocytes) are required for PMA to cause T-cell proliferation (10).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, PD tumor promoters increase killing by activated macrophages and by polymorphonuclear leukocytes through the generation of reactive forms of oxygen (26)(27)(28). PD tumor promoters are also mitogenic for a subpopulation of human T lymphocytes (29), but the activity of these cells in host defense is not known. Because Media.…”
Section: Introductionmentioning
confidence: 99%
“…TPA enhances the mitogenic effect of plant lectins on various animal lymphocytes (for review, Mastro, 1983) and is mitogenic by itself for human T cells in the presence of (greater than approximately 0 5 %) monocytes (Touraine, Hadden, Touraine, Hadden, Estensen & Good, 1977; Koretzky, Daniele & Nowell, 1982). We reasoned that the effect of TPA on bulk populations of human lymphocytes might be more easily interpreted than those arising from the plant lectins, which interact with many cell surface molecules.…”
Section: Introductionmentioning
confidence: 99%